2018
DOI: 10.1111/jdv.15054
|View full text |Cite
|
Sign up to set email alerts
|

Beta‐blockers for treatment of autoimmune blistering dermatosis

Abstract: Linked article: This article is commented on by D. Miyamoto et al., pp. e459–e461 in this issue. To view this article visit https://doi.org/10.1111/jdv.15057

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…β-Blockers have been successfully used in dermatoses such as hemangiomas, kaposiform haemangioendothelioma, pyogenic granulomas, erythemato-telangiectatic rosacea, angiolymphoid hyperplasia with eosinophillia. There have been promising results in adrenergic urticaria, aquagenic pruritus, wound healing, pemphigus vulgaris, other autoimmune blistering diseases and potentially in melanoma (58,59).…”
Section: Cutaneous Side - Effects Of β-Blockersmentioning
confidence: 99%
“…β-Blockers have been successfully used in dermatoses such as hemangiomas, kaposiform haemangioendothelioma, pyogenic granulomas, erythemato-telangiectatic rosacea, angiolymphoid hyperplasia with eosinophillia. There have been promising results in adrenergic urticaria, aquagenic pruritus, wound healing, pemphigus vulgaris, other autoimmune blistering diseases and potentially in melanoma (58,59).…”
Section: Cutaneous Side - Effects Of β-Blockersmentioning
confidence: 99%
“…Abdelmaksoud and Vestita regarding our study about the in situ expression of vascular endothelial growth factor (VEGF) and endoglin in patients with pemphigus foliaceus (PF) and pemphigus vulgaris. 1 We proposed that the severity of PF is related not only to the level of circulating autoantibodies but also to the ability to restore tissue integrity following intraepidermal detachment. We have demonstrated that overexpression of VEGF is observed both in serum samples 2 and skin fragments obtained from patients with severe PF, 3 and suggested the use of b-blockers to regulate it.…”
Section: Dear Editormentioning
confidence: 99%
“…Clinically, it has four stages: primary, secondary, latent and tertiary. 1,2 In most instances, the diagnosis is made during the secondary stage, on which lesions are more numerous, symptomatic, and may affect skin and mucosa areas simultaneously. On the other hand, the primary stage manifests by single, usually painless, ulceration that goes into spontaneously healing between 2-4 weeks after its appearance.…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation